Economic evaluation of occupational safety preventive measures in a hospital - Ramos, Delfina G. (2015)
BACKGROUND: When an organization performs an integrated analysis of risks through its Occupational Health and Safety Management System, several steps are suggested to address the implications of the identified risks. Namely, the organization should make a detailed analysis of the monetary impact for the organization of each of the preventive measures considered. However, it is also important to perform an analysis of the impact of each measure on society (externalities). OBJECTIVE: The aim of this paper is to present a case study related to the application of the proposed economic evaluation methodology. METHODS: An analysis of the work accidents in a hospital has been made. Three of the major types of accidents have been selected: needle stings, falls and excessive strain. Following the risk assessment, some preventive measures have been designed. Subsequently, the Benefit/Cost ratio (B/C) of these measures has been calculated, both in financial terms (from the organization’s perspective) and in economic terms (including the benefits for the worker and for the Society). RESULTS: While the financial ratio is only advantageous in some cases, when the externalities are taken into account, the B/C ratio increases significantly. CONCLUSIONS: It is important to consider external benefits to make decisions concerning the implementation of preventive measures in Occupational Health and Safety projects